2018
DOI: 10.1007/s10661-018-6537-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and enhancing the utility of low-cost activity and location sensors for exposure studies

Abstract: Nowadays, the advancement of mobile technology in conjunction with the introduction of the concept of exposome has provided new dynamics to the exposure studies. Since the addressing of health outcomes related to environmental stressors is crucial, the improvement of exposure assessment methodology is of paramount importance. Towards this aim, a pilot study was carried out in the two major cities of Greece (Athens, Thessaloniki), investigating the applicability of commercially available fitness monitors and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…These methods are burdensome for study participants (particularly for children) and are subject to reporting bias and/or missing data. ( 13 , 16 ) To alleviate the burden of self-reporting, several studies have used handheld( 11 , 12 , 14 , 17 ) or smartphone-based( 18 21 ) Global Positioning Systems (GPS) to estimate where participants spend their time. These studies have demonstrated that GPS sensors tend to provide accurate location data when outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are burdensome for study participants (particularly for children) and are subject to reporting bias and/or missing data. ( 13 , 16 ) To alleviate the burden of self-reporting, several studies have used handheld( 11 , 12 , 14 , 17 ) or smartphone-based( 18 21 ) Global Positioning Systems (GPS) to estimate where participants spend their time. These studies have demonstrated that GPS sensors tend to provide accurate location data when outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of potentially important environmental exposures makes developing a single 'exposome' device challenging [126]. Toward the inclusion of multiple sensors to improve the accuracy of pulmonary disease efforts, low-power solutions for integrating personal ozone exposure and volatile organic compound measures are beginning to appear [127].…”
Section: Pulmonary Health and Environmental Exposuresmentioning
confidence: 99%
“…the elderly (Waldock et al 2018)). Personal sensors are available to measure an individual's personal exposure to temperature in the same context as physical activity and location for potential use in exposome studies (Asimina et al 2018). Other understudied exposures include non-air pollutants such as mycotoxins, secondary fungal metabolites that contaminate food.…”
Section: Understudied Interactions With Physical Activitymentioning
confidence: 99%